Preparation and Ex-Vivo Evaluation of Stabilized Cefdinir Nanosuspension - Asia Abed Al-Mahmood, Shaimaa N. Abd Alhammid (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The objective of this research is to prepare cefdinir as a nanosuspension formulation to improve its solubility and dissolution rate. Cefdinir is a class IV drug with low solubility and low permeability. Methods: Eight formulations were prepared with different types of stabilizers and different concentrations including poly vinyl pyrrolidone (PVP-K90), poly vinyl alcohol (PVA), D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) and soluplus ®. Ratio of drug to stabilizer used to prepare the nanosuspension were 1:1 and 1:2. The prepared nanosuspension formulations were evaluated for particle size, entrapment efficiency, dissolution study, atomic force microscopy (AFM), transmission electron microscope (TEM), field emission scanning electron microscopy (FESEM) and differential scanning calorimetry (DSC). Results: The dissolution rate was enhanced due to a reduced particle size. The prepared nanosuspension was homogenous with a uniform size and stable cefdinir nanoparticles. Drug entrapment efficiency of F1-F8 was ranged from (78.4 ±0.1) nm to (95.11±0.01) nm. Conclusion: Enhanced solubility and better dissolution profile of cefdinir result from using solvent evaporation method. Keywords: Cefdinir, nanosuspension, Antisolvent precipitation, Stabilizer , In vitro Evaluation.